The role of Competitive Intelligence in Achieving Strategic Sovereignty - Mohamad, Dr. Mohamad A.; Naif, Nebar T.; Abdulla, Ali A. (Mitanni Journal of Humanitarian Sciences, 2023)
The current study aims to determine the extent of the availability of the dimensions of competitive intelligence among the administrative leaders of Korek Telecommunications Company in Dohuk Governorate and its impact on achieving strategic sovereignty. The problem of the study can be presented through the following research question: What is the extent of the availability of the dimensions of competitive intelligence among the administrative leaders in the organization under study and its reflection in Achieving strategic sovereignty? The questionnaire was used as the main tool for collecting data from sample members, while the data was analyzed using the arithmetic mean and standard deviation, as well as the (F and T) tests and the interpretation coefficient (R^2) using the statistical package (SPSS). The study reached a set of conclusions, the most prominent of which is that there is a significant relationship of influence to the dimensions of competitive intelligence in achieving strategic sovereignty, which was relied upon in presenting proposals consistent with it.